"I can rise up from my adversity”: Situational language learning strategies - Ismiatun, Febti; Widowati, Diah Retno; Suhartoyo, Eko (JEES (Journal of English Educators Society), 2020)
Deriving from the postulation that learning strategies are shaped from a learning situation, which is inseparable from its socio-cultural context. A paradigm has shifted language learning strategies (LLSs) studies in the new perspective of situational-based research. Using a narrative approach, this study examined one female pre-service teacher of an English education major in occupying strategies to fulfill the learning needs. To meet with the data, semi-structured interviews were carried out for the participant through a series of interconnected questions. The results marked that the use of learning strategies varied in a distinct learning situation, including the strategies to achieve the learning goal as well as to encounter the obstacles in English learning. Thus, this study has emphasized the feasibility of LLSs in context. Suggestions were also presented at the end of this paper. HIGHLIGHTS: The use of strategies is varied in changing learning situation. The appropriate strategies assist students in fulfilling the English learning needs. The application of strategy training in EFL classroom is noteworthy because it is teachable.